Breaking the silence: ICT and the elderly in Malaysia - Abd Rahim, Normaliza; Zainon Hamzah, Zaitul Azma; Sheik Said, Normahdiah; Che Su, Norizan; Salleh, Che Ibrahim (Malaysian Educational Technology Association, 2007)
In the developed world today technology plays an important role in helping people to live longer and lead better lives. The elderly who shy away from technology can expose themselves to the risks of becoming isolated and under stimulated. Most of the elderly population do not have a high degree of computer literacy, and are not so familiar with using computers. Hence, to enhance the quality of their lives, it is pertinent that our present ICT is designed to meet the needs of this population. With the emergence of ICT in Malaysia, the country is improving rapidly. Malaysia which was once mainly dependent on agriculture has moved its focus to manufacturing and information services. This has given employment opportunities to many Malaysians, and increased not only the diversity of the work force, but also the quality of their life. This does not mean, however, that the country has ignored the agriculture sector. Rather, with ICT, we are able to grow better crops and produce greater yields. As weather changes are monitored, damages due to rains and floods are minimized. Although ICT has also brought some new problems, overall, it has increased the quality of Malaysian’s lives. Here, the elderly will not be neglected and hence we do hope that ICT would continue to bring greater benefits to the Malaysians, in the future.